Pengaruh Pelatihan dan Pengembangan Karir terhadap Kinerja Karyawan PT. Cakra Kencana Lestari - Firdaus, Firdaus; Purboyo, Purboyo; Lestari, Niti (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2024)
The purpose of this study is to analyze and determine the influence of career training and development on employee performance at PT. Cakra Kencana Lestari. This research is of a quantitative type. The population in this study consists of all employees empowered at PT. Cakra Kencana Lestari. The sampling for this research is done using total sampling, which includes all the population, with a sample size of 40 employees of PT. Cakra Kencana Lestari. Based on the research results and analysis obtained in this study, it can be concluded that career training and development have a significant partial impact on employee performance at PT. Cakra Kencana Lestari. Simultaneously, career training and development have a significant impact on employee performance at PT. Cakra Kencana Lestari. The company's efforts in providing career training and development have a positive impact on employee performance.